Vzaimosvjaz' sportivno-techniceskogo rezul'tata s parametrami special'noj fiziceskoj podgotovlennosti i funkcional'nogo statusa plovcov oboego pola 15-17 let - Solopov, I. N.; Avdienko, V. B.; Fomichenko, T. G. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
It has been discovered that for swimmers aged 15-17, the sports and technical result has reliable and very significant connections with indicators of power capabilities and with the main indicators of hydrodynamics, both in young men and to a greater extent in girls. The level of sports performance of young swimmers of 15-17 years of both sexes does not have significant relationships with several indicators of the functional state of the body, except for the vegetative rate of rhythm in boys and the coefficient of variation in girls. In swimmers, both boys and girls, the sporting result has very extensive and close ties, both with biochemical and hematological indicators, most of which relate to red blood indicators and which, one way or another, determine the oxygen supply of the body.